Epidemiological Analysis of Age and Gender Disparities of Some Selected Diseases Among Children Under Five in Lagos State, Nigeria - Ayenigba, Alfred Ayo; Ajao, Olutunde Michael (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Infant mortality due to preventable infectious diseases remains a critical public health challenge in sub-Saharan Africa, particularly in resource-limited settings like Lagos State, Nigeria. This study conducted a statistical analysis of the patterns of selected diseases—malaria, measles, kwashiorkor, yellow fever, and cholera—affecting children under four years of age at Egan Primary Health Care Center in Igando, Lagos, over a one-year period (2020). Utilizing a hospital-based cross-sectional design, secondary data from 1,541 cases were analyzed using chi-square tests, relative risk (RR), and odds ratio (OR) to assess disease dependency on age, gender, and inter-disease associations. The results revealed that disease occurrence was independent of age (χ² = 857.48, p < 0.001) but showed no significant dependency on gender (χ² = 2.14, p = 0.709), though males exhibited higher susceptibility to malaria (OR = 1.33, RR = 1.15), measles (OR = 1.02), and kwashiorkor (OR = 1.16). In contrast, yellow fever (OR = 0.94) and cholera (OR = 0.96) posed slightly lower risks to males. The study highlights a high burden of childhood infectious diseases in Lagos, driven by environmental and healthcare disparities, and recommends targeted, gender-sensitive interventions to reduce under-five mortality.